Bone plastic materials and methods of their use (review) - Astapenko О. О.; Yemelianov С. Д. (Actual Dentistry, 2024)
Relevance. In case of bone deficiency or defect in the area of subsequent implantation, it is rational to perform bone grafting. There are various techniques for bone grafting operations that differ in incisions, volumes, materials, and methods of their use during surgery. When using bone grafting materials, different substrates are used for their mixing. The purpose of the work is to provide a structured understanding of the current state of development of bone grafting on the example of studies related to operations using bone grafting materials and substances for their mixing (substrates); to identify areas that have not been paid attention to. Conclusions: 1. Currently, the issue of choosing a substrate for kneading osteoplastic materials has not been sufficiently studied. 2. There is a need to conduct a study comparing different substrates for kneading bone tissue. 3. It is necessary to create scientifically based guidance on the use of different substrates for different clinical cases.